Formulation of Hospital Legal Responsibility in Sexual Violence Cases Based on Legal Certainty - Setyo Trisnadi; Andri Winjaya Laksana (UNISSULA Semarang, 2025)
Abstract. Sexual violence in hospitals is a serious legal violation that can violate the human right to a sense of security. Hospitals, which should be places of healing and recovery for patients who come to their place, have instead become places where sexual violence occurs that threaten human dignity and violate the law. Research objectives: To identify and analyze the weaknesses of hospital legal accountability, the formulation of hospital legal accountability in cases of sexual violence based on Legal Certainty. This legal research method is a social legal research design with a legislative approach method, a case approach method, and a comparative approach method. The legislative approach method is an approach method that refers to current laws and regulations. The case approach method is by conducting a review of cases of sexual violence that occurred in hospitals. The comparative method is used to compare laws and regulations and decisions from hospital management. Research results: Hospitals are required to have anti-sexual violence SOPs, professional codes of ethics, reporting mechanisms, investigation mechanisms, mediation mechanisms, and settlement decisions. Establishment of patient and employee protection units. Legal proceedings against perpetrators and negligent parties. Medical, psychological, legal, and rehabilitation services. The hospital has moral and legal responsibility towards the individual victim.